2018
DOI: 10.13189/eer.2018.060107
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Excited Oxygen Molecules in the Formation of the Secondary Ozone Layer at 87 to 97 km

Abstract: The secondary ozone layer is located at elevations of 87 to 97 km in the upper mesosphere-lower thermosphere. It overlaps with the ionospheric D-layer. Daytime intensive UV radiation is dissociating O 2 molecules to O atoms and photoexcitating O 2 molecules up to 11.07eV level. Ozone photolysis between the wavelengths of 118.7-121.6 nm produces three oxygen atoms from one ozone molecule. Collision reactions of O 2 (B 3 Σ u

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The comprehensive information related to the appropriate chemical and photochemical elementary processes in air is published in [69,[79][80][81][82][83][84]. Using this information, one can indicate the following processes (R1)-(R7), with a rate coefficient k, most relevant to the discussed issue.…”
Section: The Influence Of Uv Irradiation On the Very First Breakdown ...mentioning
confidence: 99%
“…The comprehensive information related to the appropriate chemical and photochemical elementary processes in air is published in [69,[79][80][81][82][83][84]. Using this information, one can indicate the following processes (R1)-(R7), with a rate coefficient k, most relevant to the discussed issue.…”
Section: The Influence Of Uv Irradiation On the Very First Breakdown ...mentioning
confidence: 99%
“…It has been suggested that collisions with other molecules (bimolecular mechanism) cause the self-decay. The kinetic energy per kelvin (monatomic ideal gas) is KE avg = 3×[R/2] = 3R/2; per mole it is 3.46 kJ/mol at 273 K [51]. It can be approximated that at 185 K one mole of ozone is receiving in collisions about 2 kJ of kinetic energy.…”
Section: Self-decay Of Ozonementioning
confidence: 99%